EARLY MARRIAGE MODELING IN WEST JAVA USING GEOGRAPHICALLY WEIGHTED REGRESSION - Simatupang, Marnita (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2023)
Woman early marriage defined as a marriage that happens to a woman under 16 years. Early marriage can affect the mother's and baby's health. Free sex, education, and poverty remain the three significant factors of early marriage. West Java Province is the third-highest province with cases of early marriage with 19.23% of cases in Indonesia in the year of 2020. The cases number of cases of early marriage in an area certainly has different characteristics. The proximity factor between regions can influence it. This study aims to model instances of early marriage in West Java Province by considering spatial aspects using the Geographically Weighted Regression (GWR) method. The existence of spatial dependence and heterogeneity is proven by Moran's Index and Breusch-Pagan value less than alpha (0.05). The results of GWR modeling using Gaussian Kernel Weights show that the Percentage of Woman Who Got Pregnant before 16 Years Old (X1), Average Years of Schooling for Woman (X2),  and Percentage of Poor People (X3), have significant impact of the percentage of early marriage in West Java.  The Percentage of Woman Who Got Pregnant before 16 Years Old (X1) variable and the Percentage of Poor People variable (X3) have a positively affects the percentage of early marriage in West Java Province in 2020. At the same time, Average Years of Schooling for Woman (X2) has a negative effect. Based on calculations, the best model in modeling early marriage in West Java Province is the GWR model, with an adjusted R2 value of 93.18%.